PENGARUH KEBIJAKAN PENDANAAN, KEBIJAKAN DIVIDEN, MANAJEMEN ASET DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - Nada, Aprilia Qathrun; Dillak, Vaya Juliana (EDUTECH CONSULTANT, 2018)
This study aims to determine the effect of funding policy (DER), dividend policy (DPR), asset management (FATO), and company size (SIZE) on company value (PBV) in manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The data used in this study was obtained from financial report data taken from the official website of the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The sampling technique used is perposive sampling and obtained 36 companies with a research period of 4 years, thus obtaining 144 sample data. The method of data analysis in this study is panel data regression analysis using software eviews 9.0. The results showed that simultaneous funding policy (DER), dividend policy (DPR), asset management (FATO), and company size (SIZE) had a significant effect on firm value (PBV). While partially funding policy (DER) has a significant effect on the negative direction of firm value. Dividend policy (DPR) does not significantly influence the negative direction of firm value. Asset Management (FATO) does not have a significant effect on the negative direction of firm value. Firm size (SIZE) does not have a significant effect on the positive direction of firm value.